A review on the production of P-enriched hydro/bio-char from solid waste: Transformation of P and applications of hydro/bio-char. (August 2022) - Chen, Guanyi; Wang, Junxia; Yu, Fan; Wang, Xutong; Xiao, Hui; Yan, Beibei; Cui, Xiaoqiang
Abstract: Phosphorus (P) is a necessary element for plant growth and animal health. Most P utilized by anthropogenic activities is released within the generation of various solid wastes such as sewage sludge, animal manure, and wetland plant, which increase the risk of water contamination. (Hydro)thermal treatment could be employed for solid waste treatment with the production of value-added hydro/bio-char, and the behavior of P during the thermochemical treatment process is critical for the further utilization of hydro/bio-char. This study provides a systematic review of the migration and transformation mechanisms of P during thermochemical treatment of various solid wastes, and special emphasis is given to the potential applications of P-enriched hydro/bio-char. Future challenges and perspectives in the thermal treatment of P-enriched solid waste are presented as well. The distribution and speciation of P were affected by feedstock properties, thermal technique, and reaction conditions, correspondingly affecting hydro/bio-char applications. The derived P-enriched hydro/bio-char was mainly applied as an agricultural soil amendment, P recovery source, and heavy metal sorbent, which could be adjusted by varying treatment process parameters. Additionally, potentially toxic substances, such as heavy metals in the solid waste, should be addressed during the production and application of hydro/bio-char. Overall, the production of P-enriched hydro/bio-char from solid waste is a promising route to simultaneously achieve P reclamation and solid waste treatment. Graphical abstract: Image 1 Highlights: (Hydro)thermal treatments changed the species and availability of P in biochar. Fates of P were affected by thermal technique type and reaction conditions. P-enriched biochar was mainly applied as soil amendment and heavy metal sorbent. Potentially toxic substances in the P-enriched solid waste should be noticed.